2021
DOI: 10.3390/molecules26020258
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin, a Glycosyloxyflavone in Myrica esculenta Bark Ameliorates Diabetic Nephropathy via Improving Glycemic Status, Reducing Oxidative Stress, and Suppressing Inflammation

Abstract: The present study evaluated the therapeutic potential of myricitrin (Myr), a glycosyloxyflavone extracted from Myrica esculenta bark, against diabetic nephropathy. Myr exhibited a significant hypoglycemic effect in high fat-fed and a single low-dose streptozotocin-induced type 2 diabetic (T2D) rats. Myr was found to improve glucose uptake by the skeletal muscle via activating IRS-1/PI3K/Akt/GLUT4 signaling in vitro and in vivo. Myr significantly attenuated high glucose (HG)-induced toxicity in NRK cells and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The lower level of AGEs is able to improve diabetic complications. Besides, O. stamineus enhances insulin sensitivity and improves insulin resistance through other pathways, such as the PI3k/Akt signaling pathway, the AMPK pathway, and the JNK pathway (summarized in Figure 6) [153][154][155]. The PTP1B activity might also be related to the PI3k/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The lower level of AGEs is able to improve diabetic complications. Besides, O. stamineus enhances insulin sensitivity and improves insulin resistance through other pathways, such as the PI3k/Akt signaling pathway, the AMPK pathway, and the JNK pathway (summarized in Figure 6) [153][154][155]. The PTP1B activity might also be related to the PI3k/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic conditions, the insulin signaling in the skeletal muscle is also compromised, leading to a lack of glucose utilization. The flavonoid myricitrin has been shown to activate the IRS-1/PI3K/AKT/GLUT4 signaling in both L6 muscle cells exposed to high glucose and in the soleus muscle of rats with T2D, improving the utilization of glucose in the diabetic milieu [42]. A study carried out with diabetic animals showed that the treatment with the flavonoid amentoflavone (20-40 mg/kg bw) for 8 weeks increased the level of phosphorylated AKT (Ser473) and the expression of GLUT-4 in the skeletal muscle, and that was associated with an improved peripheral glucose utilization and with a hypoglycemic effect [43].…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 99%
“…Additionally, dihydroquercetin was shown to mitigate the renal histopathological lesions associated with DN by mechanisms that may involve oxidative stress and inflammation suppression [ 79 ]. The nephroprotective action of the glycosyloxyflavone myricitrin, another compound belonging to flavonols, was found to be associated with the mitigation of oxidative stress as investigated both in vitro and in vivo, as well as to prevent renal inflammation [ 80 , 81 ]. Remarkably, vehiculation of myricitrin using solid lipid nanoparticles was shown to increment myricitrin effects in vivo [ 81 ].…”
Section: Implication Of Polyphenols In Renal Pathophysiologymentioning
confidence: 99%